Model Kepemimpinan Pendidikan Syekh Nawawi dan Ki Hajar Dewantara (Metakognisi, 2025)
The Educational Leadership of Sheikh Nawawi and Ki Hajar Dewantara, sees the two figures with a focus on the implementation of moral and ethical values in the teaching and learning process. Sheikh Nawawi emphasized religion-based education that forms noble morals, while Ki Hajar Dewantara used the Leadership Trilogy (example, enthusiasm, mandir) to create a conducive and inspiring educational climate. In this context, both show that educational leadership is not only about academic material, but also about the formation of students' character and morality. The integration of spiritual and social values in education is a significant contribution to the development of quality human resources in Indonesia. Keywords: Educational Leadership, Sheikh Nawawi, Ki Hajar Dewan Tara